The Effectiveness Of The Implementation Of The Regulation Of The Minister Of Agrarian And Spatial / Head Of The National Agency Of The Republic Of Indonesia Number 10 Of 2017 Concerning Internals In Semarang City - Laily Hakim Sejati; Fajar Fitrio Dwi Nugroho; Djauhari Djauhari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The objectives of this study were to: 1) To find out the implementation of the internship based on Minister of Agrarian and Spatial Planning / Head of the National Land Agency Number 20 of 2018 at the Semarang City Land Office 2) To determine the effectiveness of the implementation of the Minister of Agrarian and Spatial Planning / Head of the National Land Agency Republic of Indonesia Number 20 of 2018 concerning Internships at Semarang City Land Office 3) To find out the obstacles and solutions in the implementation of internships at the Semarang City Land Office. The data used in this study are premier data, secondary data and tertiary data that can support the assessment, which is then analyzed by descriptive analysis method.Based on the results of data analysis, it can be concluded that: 1) The implementation of an internship based on the Regulation of the Minister of Agrarian and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 20 Year 2018 in Semarang City regarding the internship in Semarang is carried out for 6 months at the Land Office. transfer of rights, land acquisition and dispute. 2) The effectiveness of the apprenticeship is considered effective in accordance with Article 9 of the regulation, namely the process of activities and land services, the process of receiving and examining the deeds listed, and the process of checking the juridical data of applications for land rights. 3) Obstacles to the implementation of the Minister of Agrarian and Spatial Planning / Head of the National Land Agency of the Republic of Indonesia Number 20 of 2018 at the Semarang City Land Office are the absence of a system of change between the National Land Agency at the center (Kota Semarang) and at Home Services. Because it is considered when doing an apprenticeship at the Land Office, the center of the scope is more.Keywords: Effectiveness, Implementation, Internship.